The effect of a psychological skills training program on mental toughness and shooting performance of 15-16 year old netball players / Jamatul Shahidah Shaari - Jamatul Shahidah , Shaari (2019)
The importance of being physically prepared is essential to ensure an athlete’s competitiveness; however, preparing the mind is similarly as critical. It is recognized that the strategies used for mental preparation can offer a resource for overcoming the kinds of situations that some athletes might face. This study is motivated by three research questions: (1) Is there any difference in the mean score of the mental toughness domains between pre- and post-intervention? (2) Is there a difference in the impact of the three groups on netball players’ mental toughness between pre- and post-intervention? (3) Is there a difference in the impact of the three groups on netball players’ shooting performance between pre- and post-intervention? Previous research has shown that one of the mechanisms for developing mental toughness in athletes is to incorporate psychological skills training as part of athlete training. What has not been examined is the efficacy of combining two specific mental skills that is easier and simpler to practice and may produce positive effects similar to other studies that have used different multimodal strategies. To bridge this gap, this study proposed an experimental approach utilizing an 8-week intervention among 46 netball players to answer the research questions. The results reveal that the athletes need special attention regarding negative energy control and attention control. The mean score of negative energy control was M = 18.33 + 3.68 during pre-intervention and M = 19.52 + 4.63 during post-intervention. Meanwhile, the mean score of attention control during pre-intervention was M = 19.11 + 2.30 and M = 19.76 + 4.17 during post-intervention. Greater attention should be given to these factors based on their respective progress scores, which are lower than other domains. Furthermore, the statistical analysis used a split-plot analysis of variance indicated that there was no significant interaction between groups across pre-test to post-test (Wilks Lambda = .953, F(2, 43) = 1.067, p = .353, partial eta squared = .047) on athletes’ mental toughness score. However, the study showed that the main effect from comparing the groups was significant, F(1, 43 = 11.800, p < .001) for shooting performance across the two time periods. The results of the study indicate that the subjects in Group 1 and Group 2 had effectively increased their shooting performance. It was also shown that Group 1 had better shooting skill performance than Group 2 and the control group. Psychological skills training interventions have been proven effective in improving shooting performance and might be the key for supporting works that aim to design an intervention for enhancing athletes’ mental toughness. Future studies could explore the implications of purposefully-developed psychological-skills training program based on the weakness domains of mental toughness. It is recommended that this study be replicated for other sport skills.